Climate change in agricultural production and migration intentions in developing countries: Evidence from african countries - Diallo, Mamadou Abdoulaye; Bazie, Porto (Asian Journal of Empirical Research, 2025)
This study aims to assess the effect of climate change on agricultural production and its impact on migration intentions. We conceptualize migration intention as a process ranging from desire and planning to preparation. Using data from round 7 (2016/2017) of Afrobarometer surveys, we estimate a sequential logit model on a sample of 44,224 adults in 33 African countries. Descriptive results show that 36% of adults express a desire to migrate, 14% plan to leave within two years, and only 3% are preparing to migrate. Econometric estimates indicate that worsening climatic conditions in agricultural production increase the likelihood of migration intentions. The study also identifies several factors affecting migration intentions, such as age (with younger individuals more likely to migrate), gender (women show lower migration intentions), education level, internet usage, and dependency on remittances. Additionally, political commitment and perceptions of governance play a role. The findings emphasize the importance of incorporating climate change into public policies, particularly migration policies. The study recommends focusing on improving living conditions for the younger, more educated population, those dissatisfied with governance, and those dependent on remittances, to better address migration challenges linked to climate change.